The pharmaceutical family Draškoci and its social contribution to the development of the town of Svilajnac and the environment - Matić, Jelena; Krajnović, Dušanka (Archives of Pharmacy, 2022)
After the announcement of the international competition and the adoption of the Law on Pharmacies in 1865, numerous medical experts came to Serbia. The noble pharmaceutical family Draškoci moved from Slovakia to Belgrade in search of a better life in 1868. This paper aims to determine the significance and social contribution of the pharmaceutical family Draškoci to the economic and cultural life of the town of Svilajnac in the aforementioned period. Julije Draškoci opened the first pharmacy in Svilajnac on the 24th of April 1875. After the foundation of the gymnasium in Svilajnac in 1877, he voluntarily taught for free gymnastics, physics and chemistry in that school. He was engaged in fruit and vineyard, cattle breading, and apiculture. He was the originator of mountaineering in Resava and Serbia, and the initiator of the school excursions. He was one of the founders of the Resava Savings Bank in 1885. He founded the Resava Shooting Club in 1891. Of his ten children, only his son William completed studies in pharmacy in Vienna, like him, and continued to run his father’s pharmacy until its nationalization in 1949. He participated in the Balkan Wars and the First World War. The people of Svilajnac will remember the Draškoci family for their exceptional contribution to the development of town and social life, and the pharmacist William especially for saving several of his fellow citizens from being shot during the Second World War.